Potential of reduction of greenhouse gases emissions in ukraine on period to 2020 year - Гальперіна, Л.П.; Костюковський, Б.А.; Мовчан, Я.І.; Скрипниченко, М.І.; Запорожець, О.І.; Шумська, С.С. (Proceedings of National Aviation University (archive), 2010)
Article is devoted to the assessment of potential of green-house gases mitigation, taking into account basic priorities of national development and providing an implementation of international obligations of Ukraine in this question after 2012 year. A macroeconomic and particular branch forecasting of national development was carried out, basic scenarios were defined, an analysis and estimation of technological potential of measures on reduction of green-house gases due to different scenarios were done on a period between 2010−2020 years. Recommendations are given in relation to optimization of energy-efficient approaches in Ukraine.